Di--thiocyanato-2N: S; 2S: N-bis [bis (2-methyl-1H-benzimidazole-N3)(thiocyanato-N) cadmium (II)] - Ahaker, S.; Mohd Ali, H.; Khaledi, H. (2010)
The title compound, [Cd2(NCS)4(C8H8N2)4], is a centrosymmetric dinuclear cadmium(II) complex in which each two metal ions are linked by a pair of thiocyanate N:S-bridges. Two 2-methylbenzimidazole N-atom donors and one terminal thiocyanate N atom complete a highly distorted squarepyramidal geometry around the Cd atom. In the crystal structure, two N—H S hydrogen-bonding interactions occur, resulting in a three-dimensional polymeric structure. The apical 2-methylbenzimidazole ring and its symmetryrelated counterpart are arranged in an antiparallel manner with a centroid–centroid separation of 3.6050 (14) A ° , indicative of a – interaction.